USE OF ZEOLITE, SAND AND SOIL AS PLANTING MEDIA WITH GRASS AND LEGUMINOCEAE AS A HOST PLANT IN MASS PRODUCTION OF MYCORRHIZA ARBUSCULA - P. D. M. H. Karti; Setiana Setiana; M. A. Ariyanti; G. J. Kusumawati R. (Jurnal Zeolit Indonesia, 2006)
Planting media and host crop play an important role in determining inoculum mass production of Mycorrhiza arbuskula (CMA). Planting media used in this research consist of zeolite, sand, and soil and the host crop are S. bicolor, S. splendida, C. javanica, C. pubescens. Host crop S. bicolor could be respectively replaced by S. splendida with zeolite as the best planting media in order to produce mass of CMA. In the other hand, mass production of CMA by the combination of S. splendida and soil as planting media could work well under condition that inoculum added in twofold dosage. Using of P. javanica and C. pubescens with zeolite as a planting media was found as the best combination. And the combination of C. pubescens and soil as a planting media could be used also under condition that inoculum added in twofold dosage.